The prevalence of Dupuytren contractures in patients with psoriasis. (1st December 2014) - Patel, M.; Freeman, N. R.; Dhaliwal, S.; Wright, N.; Daoud, Y.; Ryan, C.; Dibella, A. V.; Menter, A.
Summary: Background: Dupuytren contracture (DC) is a fibrocontractile disease of the palms, affecting approximately 4% of the population, while psoriasis is an immune‐mediated disease, affecting 2% of the population. Through clinical observation in our psoriasis clinic, we found an apparent increased prevalence of DC in patients with psoriasis compared with the general population. This has not previously been statistically verified in a clinical study. Aim: To evaluate the prevalence of DC in the full range of clinical psoriasis phenotypes. Methods: In total, 98 patients with psoriasis attending our psoriasis clinic were examined for DC, based on predetermined criteria. In addition, 84 patients with DC, obtained from a specialist hand clinic, were assessed using a validated psoriasis questionnaire. We utilized Bayes theorem and bootstrap simulation to calculate the conditional prevalence of DC, then we used the results to compare the prevalence of DC between patients with psoriasis and a nonpsoriasis population. Results: The percentage of patients with DC was 19.6% in the psoriasis population and 3.6% in the nonpsoriasis population. Development of DC showed a phenotypic predilection, with 39.1% of patients with predominantly palmoplantar involvement and 38.9% of patients with intertriginous psoriasis developing DC compared with 12.7% of patients with psoriasis who did not have these two phenotypical presentations. Conclusions: Our data show a positive correlation between psoriasis and DC. Patients with the palmoplantar phenotype of psoriasis were more likely to develop DC. By understanding this relationship, dermatologists may diagnose DC early in its onset in patients with psoriasis, prompting referral to hand surgeons when appropriate.